Investigating the Factors that Motivate MSME owners in South Tangerang to use QRIS - Saraswati, Fitri; K, Syifa Qiani; S, Synthia Atas (West Science Business and Management, 2025)
The focus of this research is the identification and evaluation of factors that influence the use of QRIS as a digital payment tool technology for transactions. MSMEs, especially in South Tangerang, who use QRIS as a digital payment tool are the respondents involved in this research. The research method used in this research is a quantitative research method and the type of research used in this research is descriptive. The population taken is located in the MSMEs in the South Tangerang area, precisely in Pasar Delapan which has 100 restaurants. The Result of the research are Knowledge influences Attitude Toward Using QRIS, Trust has no effect on Attitude Toward Using QRIS, Perceived Ease of Use influences Attitude Toward Using QRIS, Perceived Usefulness has no effect on Attitude Toward Using QRIS, Attitude Toward Using QRIS has no effect on Actual system use of QRIS, Knowledge influences the Actual system use of QRIS, Trust influences the Actual system use of QRIS, Perceived Ease of Use influences the Actual system use of QRIS, Perceived Usefulness has no influences the Actual system use of QRIS, Knowledge and Attitude Toward Using QRIS has no effect on Actual system use of QRIS, Trust and Attitude Toward Using QRIS has no effect on Actual system use of QRIS, Perceived Ease of Use and Attitude Toward Using QRIS has no effect on Actual system use of QRIS and Perceived Usefulness and Attitude Toward Using QRIS has no effect on Actual system use of QRIS